2020
DOI: 10.1097/aud.0000000000000922
|View full text |Cite
|
Sign up to set email alerts
|

Place-Pitch Interval Perception With a Cochlear Implant

Abstract: Objectives: Pitch is poorly perceived by cochlear implant (CI) users. However, as it is not well understood how pitch is encoded with electric stimulation, improving pitch representation with a CI is challenging. Changes in place of stimulation along the cochlea have been described as changes in pitch and can be accurately ranked by CI users. However, it remains unknown if place-pitch can be used to encode musical intervals, which are a necessary attribute of pitch. The objective of these experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…Six of the 10 subjects used the advanced combination encoder (ACE) sound coding strategy which provides no useful temporal cues in response to pure tones ( Stupak et al, 2021 ; Swanson et al, 2009 ) and one used HiRes Optima-P which provides reliable temporal cues only for pure tones above 306 Hz (Appendix of Stupak et al, 2021 ). However, the two subjects using FS4 or FS4p strategies were provided reliable temporal and place cues in response to the pure tones (Appendix of Stupak et al, 2021 ). Sung vowels are more complicated stimuli which provide both place and temporal modulation cues through a processor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Six of the 10 subjects used the advanced combination encoder (ACE) sound coding strategy which provides no useful temporal cues in response to pure tones ( Stupak et al, 2021 ; Swanson et al, 2009 ) and one used HiRes Optima-P which provides reliable temporal cues only for pure tones above 306 Hz (Appendix of Stupak et al, 2021 ). However, the two subjects using FS4 or FS4p strategies were provided reliable temporal and place cues in response to the pure tones (Appendix of Stupak et al, 2021 ). Sung vowels are more complicated stimuli which provide both place and temporal modulation cues through a processor.…”
Section: Discussionmentioning
confidence: 99%
“…Place coding can also distort perceived intervals. Using x-ray data from Landsberger et al (2015) , Stupak et al (2021) documented that the average number of semitones per degree represented by the default frequency allocation was smaller than the number of semitones per degree represented by the corresponding characteristic frequency (CF) of the spiral ganglion ( Stakhovskaya et al, 2007 ). Although the number of semitones per degree varied considerably across insertions and devices, the compression of intervals across the cochlea was consistently found for all manufacturers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies have shown that cochlear implant users have poor interval identification compared to their normal-hearing peers, especially above middle C. Pitch and relative intervals can be conveyed by stimulation timing (i.e., the modulation or stimulation rate) but with much variability in pitch salience and in the upper frequency that can be conveyed by stimulation rate ( Pijl and Schwarz, 1995a , b ; Pijl, 1997 ; Todd et al, 2017 ). Place cues for pitch (i.e., active electrodes and stimulation configuration) provide a strong sense of pitch but one that is compressed compared to normal ( Stupak et al, 2021 ). Stupak et al (2021) found consistent warping of intervals amongst cochlear implant users, suggesting the ability to perceive intervals is likely not linked to duration of deafness.…”
Section: Introductionmentioning
confidence: 99%
“…Place cues for pitch (i.e., active electrodes and stimulation configuration) provide a strong sense of pitch but one that is compressed compared to normal ( Stupak et al, 2021 ). Stupak et al (2021) found consistent warping of intervals amongst cochlear implant users, suggesting the ability to perceive intervals is likely not linked to duration of deafness. Spitzer et al (2021) investigated musical interval distortion in cochlear implant users who had normal hearing in their non-implanted ear (i.e., single-sided deafness).…”
Section: Introductionmentioning
confidence: 99%